Evaluation of Natalizumab Pharmacokinetics and Pharmacodynamics: Toward Individualized Doses - Serra López-Matencio, Jose M.; Pérez García, Yaiza; Meca-Lallana, Virginia; Juárez-Sánchez, Raquel; Ursa, Angeles; Vega-Piris, Lorena; Pascual-Salcedo, Dora; de Vries, Annick; Rispens, Theo; Muñoz-Calleja, Cecilia (Frontiers in Neurology, 2021)
Background: Plasma concentration of natalizumab falls above the therapeutic threshold in many patients who, therefore, receive more natalizumab than necessary and have higher risk of progressive multifocal leukoencephalopathy. Objective: To assess in a single study the individual and treatment characteristics that influence the pharmacokinetics and pharmacodynamics of natalizumab in multiple sclerosis (MS) patients in the real-world practice. Methods: Prospective observational study to analyse the impact of body weight, height, body surface area, body mass index, gender, age, treatment duration, and dosage scheme on natalizumab concentrations and the occupancy of α4-integrin receptor (RO) by natalizumab. Results: Natalizumab concentrations ranged from 0.72 to 67 μg/ml, and RO from 26 to 100%. Body mass index inversely associated with natalizumab concentration (beta = −1.78; p ≤ 0.001), as it did body weight (beta = −0.34; p = 0.001), but not height, body surface area, age or gender Extended vs. standard dose scheme, but not treatment duration, was inversely associated with natalizumab concentration (beta = −7.92; p = 0.016). Similar to natalizumab concentration, body mass index (beta = −1.39; p = 0.001) and weight (beta = −0.31; p = 0.001) inversely impacted RO. Finally, there was a strong direct linear correlation between serum concentrations and RO until 9 μg/ml (rho = 0.71; p = 0.003). Nevertheless, most patients had higher concentrations of natalizumab resulting in the saturation of the integrin. Conclusions: Body mass index and dosing interval are the main variables found to influence the pharmacology of natalizumab. Plasma concentration of natalizumab and/or RO are wide variable among patients and should be routinely measured to personalize treatment and, therefore, avoid either over and underdosing.